Entrapment of Common Peroneal Nerve by Surgical Suture following Distal Biceps Femoris Tendon Repair - Aki Fukuda; Akinobu Nishimura; Shigeto Nakazora; Ko Kato; Akihiro Sudo (Case Reports in Orthopedics)
We describe entrapment of the common peroneal nerve by a suture after surgical repair of the distal biceps femoris tendon. Complete rupture of the distal biceps femoris tendon of a 16-year-old male athlete was surgically repaired. Postoperative common peroneal nerve palsy was evident, but conservative treatment did not cause any neurological improvement. Reexploration revealed that the common peroneal nerve was entrapped by the surgical suture. Complete removal of the suture and external neurolysis significantly improved the palsy. The common peroneal nerve is prone to damage as a result of its close proximity to the biceps femoris tendon and it should be identified during surgical repair of a ruptured distal biceps femoris tendon.